Global studies : - Husain, Mir Zohair (McGraw-Hill/Contemporary Learning Series, 2006)
Maintains that we are living in a globally interdependent world in which it is imperative for the non-Muslim world to understand the faith of 1.3 billion Muslims who live all over the world. This book also provides readers with a list of annotated Internet sites on Islam, and a list of articles and books on Islam and the Muslim world.